How important are global factors for understanding the dynamics of international capital flows?. (December 2020) - Eller, Markus; Huber, Florian; Schuberth, Helene
Highlights: Global factors explain the lion share of country-specific capital flow volatility. Global factors became more important after the global financial crisis. Some domestic factors can insulate economies from the global financial cycle. Analysis based on a time-varying parameter factor model with stochastic volatility. Abstract: We propose a dynamic factor model with time-varying parameters and stochastic volatility to analyze the relationship between global factors and country-specific capital flow dynamics. Studying a global sample of 43 countries from 1994 until 2015, we show that global co-movement of macroeconomic, financial and capital flow variables can explain a major share of country-specific capital flow volatility and that the impact of these variables has become even more important in the aftermath of the 2008–2009 global financial crisis. Our results indicate that country-specific changes in capital flows are strongly affected by fluctuations in global financial cycles and – to some extent – by global real business cycles. We provide also some evidence that the exchange rate regime, the stock of reserves, prudent fiscal policy and more developed stock markets can insulate economies, at least partially, from the global financial cycle.